Воспитание и обучение слепого дошкольника - Солнцева Людмила Ивановна (Просвещение, 1967)
Экземпляры: КХ (20140731) / Инвентарный номер: 0176914 / Цена: 0.54 / Сис.шифр: 371.9 / Авт.знак: В 77 / ГРНТИ: 14 / ББК: 74